Algorithms of ionospheric anomalies detection in “Aurora” system of operational data analysis - Polozov, Yuryi; Fetisova, Nadezhda (E3S web of conferences, 2018)
Algorithms for ionospheric data processing are presented in the paper. The algorithms are implemented in the real-time mode of ionospheric parameter analysis. They are a component of “Aurora” software system for geophysical data analysis. The algorithms allow us to estimate the state of the ionosphere in the region of Kamchatka Peninsula and to detect ionospheric anomalies. Assessment of the algorithms efficiency has shown that it is possible to use them to detect ionospheric anomalies that may occur on the eve of magnetic storms. The research is supported by the Russian Science Foundation Grant (Project No. 14-11-00194).